Language learning for refugee women in the wake of the COVID-19 pandemic: Restorative pedagogies for integrating to place—Perspectives from Scotland - Cox, Sarah; Phipps, Alison; Hirsu, Lavinia (Frontiers in Communication, 2022)
As we reflect and learn from the lessons lived during the Covid-19 pandemic that severely disrupted our ways of being in the world, in this article we call for restorative pedagogies which can reconnect us to each other and to the places we live in. We present the language learning needs and experiences of four newly arrived refugee women in Scotland. A language learning study was designed using ecological methodological approaches, an iterative spiral of critical participatory action research (CPAR), and the emergent framework of permaculture design of ‘earth share; fair share; people share.’ The 5-month study included fourteen two-hour learning sessions and an initial pilot spanning across four 2-hour learning sessions. The innovative restorative pedagogy, as we propose it here, connects language learning to translanguaging practices, processes of acclimatising into a new environment, into new rituals and embodied experiences, moving inside and outside of the ‘classroom’ and with the understanding of ‘layered simultaneity’ of languages brought from and lived in multiple places. We conclude this article with reflections on the impact of these language experiences not only on designing language programmes for the integration of refugees in new communities, but also as an ethical practice for all of us in moments of crisis, when our most profound relations and habits are threatened or broken. A restorative pedagogy builds on language that respects human dignity, acknowledges the importance of place and land we walk on, and cultivates sustainable human connections in a vulnerable and unstable world.